The factors of Malaysian Banks' profitability after merger and acquisition/ Nur Syamimi Mazlan - Mazlan, Nur Syamimi (2017)
During the Asian financial crisis in year 1997, countries under International Monetary Fund (IMF) program are required to close down the small and weakest banking institutions. However, Malaysia government denied and initiated a bank merger program to restructure all the fifty four financial institutions into ten anchor banks in year 1999. Previously, many studies were done according this issue by using Data Envelopment Analysis (DEA) to study the effects of merger on Malaysia bank efficiency. However, the impact of merger and acquisition of Malaysian Bank is still vague. Hence, this study attempts to examine the factors that affect the profitability of bank after merging. In this study, financial analysis is used to see the relationship between the bank's profitability with the bank's liquidity ratio, business earning ability, and cost efficiency.